Factors Affecting Sugarcane Supply in Panji and Wringin Anom Sugar Factories - Lawado, Nadhira Maulida Rizdanti; Aji, Joni Murti Mulyo (JSEP (Journal of Social and Agricultural Economics), 2023)
Ensuring a harmonious match between the volume of sugarcane and the milling capacity is crucial for achieving an efficient production process. The yearly fluctuations in sugarcane supply depend on the consistency of the raw material and the adaptability of sugar factories to varying supply levels. This study aims to identify the factors that influence sugarcane supply, its uninterrupted flow, and its impact on revenue generation at the "PG Panji" and "PG Wringin Anom" Sugar Factories (PGs). Utilizing both descriptive and analytical methodologies, this study relies on secondary data gathered from Sugar Factories spanning the years 2011 to 2021. The data undergoes analysis using the Multiple Linear Regression Method and Trend Analysis. The results reveal that for PG Panji, sugarcane supply is influenced by factors such as farmers' land area and sugarcane productivity. Conversely, for PG Wringin Anom, supply is influenced by farmers' land area and sucrose yield (rendemen). Over the period from 2011 to 2021, sugarcane supply exhibited fluctuations, with a subsequent downward trend from 2022 to 2026, as indicated by a negative trend. Furthermore, the study discerns that the sugarcane supply does not significantly impact PG Panji's income. However, it does have an influence on the income of PG Wringin Anom. This divergence can be attributed to the distinct approaches adopted by both sugar factories in their sugarcane procurement system (inbound logistics).